Construction of Computer Software Development System Based on Artificial Intelligence - Zhang, Yuxin (2023 International Conference on Mechatronics, IoT and Industrial Informatics (ICMIII), 2023)
With the improvement of people's living standard, the technical requirements are gradually improved. Computers have penetrated into our daily life, and the development of computers is mainly from simple to complex. When it comes to computers, it is inseparable from the discussion of computer software development, and software development language is the important support of software research and development. This paper studies the development of computer software based on AI (artificial intelligence) technology, and constructs a computer software development system in this paper. Through the research, it shows that there is a trend of SCI papers in 2013-2022 through the application of AI in computer software development. From the data, it can be seen that with the increase of years, there is an obvious upward trend. From the data, it can be seen that up to now, 720 papers have been published in 2022. It can be seen that there is still a trend to apply AI technology to computer software development. With a decisive advantage, AI technology has solved many important problems for computer software development, greatly improved the quality and efficiency of software development, and met people's requirements for complex computer structures, thus continuously improving the intelligence level of computer software.